Movimiento operário no Brasil / Edgard Carone - Carone, Edgard (Corpo e alma do Brasil)
Contiene : Vol. I (1877-1944). - 2° ed. - 1984. - 486 p. - (n.56) Vol. II (1945-1964). - 1981. - XXVIII, 276 p. - (n.59) Vol III (1964-1984). - 1984. - 313 p.